2013
DOI: 10.1063/1.4809546
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced infra-red emission from sub-millimeter microelectromechanical systems micro hotplates via inkjet deposited carbon nanoparticles and fullerenes

Abstract: In this paper, we demonstrate a micro-inkjet printing technique as a reproducible post-process for the deposition of carbon nanoparticles and fullerene adlayers onto fully CMOS compatible micro-electro-mechanical silicon-on-insulator infrared (IR) light sources to enhance their infrared emission. We show experimentally a significant increase in the infrared emission efficiency of the coated emitters. We numerically validate these findings with models suggesting a dominant performance increase for wavelengths &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Although readily available, bulbs provide a cumbersome radiation source, compared to newer technology such as micro hotplates. In particular, SOI IR emitters have greater reliability, faster response and smaller physical dimensions [14,15]. Exhaled gas is difficult to store and transport [16], thus sampling breath-by-breath is our preferred method.…”
Section: Ndir Sensorsmentioning
confidence: 99%
“…Although readily available, bulbs provide a cumbersome radiation source, compared to newer technology such as micro hotplates. In particular, SOI IR emitters have greater reliability, faster response and smaller physical dimensions [14,15]. Exhaled gas is difficult to store and transport [16], thus sampling breath-by-breath is our preferred method.…”
Section: Ndir Sensorsmentioning
confidence: 99%
“…r temperature does not ut in the CO 2 absorption k's equation. We have ntally observed that the sivity, of our emitters is m [18]. Herein, we employ h have high wavelengthance the thermo-optical mprovement was assessed t of a commercial high 5, Excelitas) to a CNTin the presence of 100% er and the detector were rical chamber ~7 cm apart using digital mass flow cat).…”
Section: Cnt Growth and Charactementioning
confidence: 99%
“…The coupling between CMOS technologies and micromachining fabrication techniques offers one viable and attractive route to achieve high-throughput manufacturing, in a cost efficient production process. Nevertheless, materials commonly used in CMOS foundries are often not pyroelectric and have poor IR absorption properties especially for wavelengths < 8 µm, 3 a spectral window of importance for NDIR gas sensing (e.g. methane and CO 2 ).…”
Section: Manuscriptmentioning
confidence: 99%